PENDEKATAN IDEALISME DALAM PEMBELAJARAN BERBASIS TEKNOLOGI: ANALISIS FILOSOFIS TERHADAP PENDIDIKAN DIGITAL - Rosiana Rosiana; Athiqotul Maghfiroh; Tatsbita Ramadhani; Dinda Rahmawati; Muhlisin Muhlisin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the application of idealism philosophy in the context of technology-based learning in the digital era. The main focus of this study includes the fundamental concepts of idealism that emphasize intellectual, moral, and spiritual development through metaphysical, epistemological, and axiological aspects. This qualitative research based on library study employs a descriptive-analytical philosophical concept analysis method using content analysis techniques, philosophical interpretation, and radical deduction. In the digital era, educators from the perspective of idealism have a central role as value guides, moral role models, and facilitators of students’ personality development rather than merely delivering technical materials. The results of the analysis indicate that the integration of character values such as discipline and responsibility can be implemented through digital platforms such as e-learning and Learning Management Systems (LMS). However, significant challenges arise in the form of technological distractions, negative influences of social media, and the lack of teachers’ readiness in designing value-based digital learning. In conclusion, technology-based learning from the perspective of idealism should be able to balance technological advancement with the strengthening of universal values in order to develop individuals who are intellectually and morally complete